The Association between Organisational Commitment and Talent Retention Practices:A study on Malaysian SMEs - Chang, Wei Lin (2017)
This study addresses the gap between predictors of organisational commitment and talent retention practices adopted by Malaysian small-medium enterprises (SME). More specifically, the study explores three research objectives: (1) the predictors of organisational commitment;(2) talent acquisition practices adopted by Malaysian SMEs; and (3) gap between talent retention practices adopted by Malaysian SMEs and best practices. The current study employed a mixture of quantitative and qualitative research design. Data was collected via online questionnaire from 102 respondents working in Malaysian SMEs and semi-structured interviews with three owner-managers of Malaysian SMEs. The findings revealed that freedom and job autonomy, and reward & recognition are significant predictors of organisational commitment. Satisfaction on supervision is calculated as moderately correlated to organisational commitment but not a significant predictor of it. Five main themes were collected from the semi-structured interviews, including, but not limited to informal workload, strategies to attract potential talents, challenges faced during talent selection process, strategies in determining the right ‘fit’, and their talent retention process. There appears to be a gap between talent retention practices adopted by Malaysian SMEs and best practices but findings from binomial test suggested that the proportion of committed employees are more than 0.50. Hence, it was interesting to explore the characteristics of Malaysian SMEs and strategies used by owner-managers to stay competitive in the volatile business market. Nevertheless, recommendations for managers of Malaysian SMEs to further improve the retention rates were discussed, including a periodic review of employee’s pay, forming alliances with institutions, having a forum for employees to raise their concerns and employers to share their opinions and feedbacks. Limitations of current study and implications for future research as well as other areas that warrant further research were also discussed.